An Analysis of English Language Learning Interest at Eleventh Grade Students of SMAN 2 Muaro Jambi - Nazira, Alfiodhea; Wennyta, Wennyta; Dewi, Kartika (JELT: Journal of English Language Teaching, 2025)
This research was conducted on eleventh grade students of SMA N 2 Muaro Jambi. The purpose of this study was to determine students' interest in learning English with five indicators, namely: attention, motivation, pleasure, perception, and activity. In this case, the research design used was quantitative research. The population of this study was eleventh grade students, while the sample was selected using cluster random sampling. There were 36 samples involved. This study used a questionnaire instrument with a total of 20 questions. The data analysis technique used was to calculate student scores and analyze using SPSS. The analysis results show that the attention indicator shows an average score ranging from 2.75 to 2.97. The motivation indicator has an average score ranging from 2.47 to 2.75. In the pleasure indicator, the average score ranges from 2.31 to 2.81. The perception indicator showed an average score between 2.64 to 2.81. The activity indicator showed a more positive response with an average score between 2.72 to 3.03. Overall, the total score of learning interest shows an average value of 54.83 with a median value of 56.00 which indicates that most students have an interest in learning in the “Less Interested” category.